Transgenic Ascidians (Advances in Experimental Medicine and Biology, 2018)
This book comprehensively describes the transgenesis techniques and applied experimental methods in ascidians including enthusiastically developed original devices in addition to concrete examples of developmental biology studies. Ascidians have been one of the most important model animals in developmental biology for studying molecular and cellular processes underlying formation of the chordate body plan. Transgenic techniques such as microinjection, electropolation, cis-element analysis and application, and TALENs and CRISPR/Cas9 have been developed in ascidians for more than 20 years, and now many applied methods, some of which are unique in ascidians, have been accumulated. Those extensive technological innovations, such as cell isolation, cell labeling, germ-line transformation, marker transgenic lines, and the experimental systems for studying notochord formation and nervous system, are exceptional particularly in marine invertebrates. This book is useful for ascidian researchers to quickly access the techniques in which they are interested as well as to compare each technology to become familiar with specialized tips, and for biologists of other organisms to learn the unique techniques and ingenious attempts specific to ascidians. Providing detailed and easily understandable descriptions of techniques, the book will inspire ascidian specialists to improve their techniques, encourage anyone wanting to begin studying ascidians, and enable readers to immediately apply the techniques to the organisms they research.